Peran penyuluh terhadap aktivitas kelompok tani di Desa Ellak Laok Kecamatan Lenteng Kabupaten Sumenep - Arifin, Ayu; Suprapti, Isdiana; Ihsannudin, Ihsannudin (Universitas Trunojoyo Madura, 2025)
Indonesian agriculture is currently being identified as having a fairly slow development. Thus, it is important to have agricultural extension services to foster motivation for the community in carrying out agricultural development in Indonesia. The purpose of this study is 1) to know the role of extension workers in Ellak Laok Village, 2) to know the factors that influence the activities of farmer groups in Ellak Laok Village. The study was conducted in Ellak Laok Village, Lenteng Sumenep District, with a sample of 70 respondents determined by Arikunto's theory. Simple random sampling method used in sampling. Processing data using descriptive analysis and multiple linear regression analysis. The results of the study found that the role of extension workers as motivators and communicators was included in the very good category, the role of extension workers as educators, organizers and catalysts was included in the good category and the role of extension workers as communicators in the medium category. Factors that influence the activities of farmer groups are the role of extension workers as motivators (X1), educators (X2), facilitators (X3), communicators (X4), organizers (X5) and catalysts (X6).